Meeting future food demand with current agricultural resources. (July 2016) - Davis, Kyle F.; Gephart, Jessica A.; Emery, Kyle A.; Leach, Allison M.; Galloway, James N.; D'Odorico, Paolo
Highlights: The global food system requires large amounts of water, nitrogen, CO2, and land. We project these requirements and emissions to 2050 under future diet scenarios. Even with improved efficiencies, agriculture's environmental burden will grow. Alternative diets and improved efficiency can reduce the food system's impacts. Abstract: Meeting the food needs of the growing and increasingly affluent human population with the planet's limited resources is a major challenge of our time. Seen as the preferred approach to global food security issues, 'sustainable intensification' is the enhancement of crop yields while minimizing environmental impacts and preserving the ability of future generations to use the land. It is still unclear to what extent sustainable intensification would allow humanity to meet its demand for food commodities. Here we use the footprints for water, nitrogen, carbon and land to quantitatively evaluate resource demands and greenhouse gas (GHG) emissions of future agriculture and investigate whether an increase in these environmental burdens of food production can be avoided under a variety of dietary scenarios. We calculate average footprints of the current diet and find that animal products account for 43–87% of an individual's environmental burden – compared to 18% of caloric intake and 39% of protein intake. Interestingly, we find that projected improvements in production efficiency would be insufficient to meet future food demand without also increasing the total environmental burden of food production. Transitioning to less impactful diets would in many cases allow production efficiency to keep pace with growth in human demand while minimizing the food system's environmental burden. This study provides a useful approach for evaluating the attainability of sustainable targets and for better integrating food security and environmental impacts.